Wpływ wybranych czynników na wykorzystywanie i opracowywanie planów w bankach spółdzielczych w Polsce - Siudek, Tomasz (Impact of Chosen Factors on Taking Advantage and Elaborating Plans in Cooperative Banks in Poland, 2007)
The author determines the impact of chosen factors, that is: the size of ownership capitals and assets in all cooperative banks, kind of organisation, the type of communes, the region of led activity, as well as the level of the ROA remunerativeness for taking advantage and elaborating plans in cooperative banks in Poland. The obtained data show that only the size of ownership capitals of cooperative banks had statistically significant influence on the level of planning usage in cooperative banks management. Other factors did not have statistically significant influence.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1174, s. 443-453